Respuesta :
First, you combine like terms. On the left you would subtract the x from 2x giving you 1+x=x-5+x. On the right you add x to x to get 2x, 1+x=2x-5. Then, you move the smallest coefficient, this being the x, to the other side. 1=x-5. Finally, you add t to both sides to give you 6=x.
x = 6
Step by step:
First, collect like terms:
1 + 2x - x = x - 5 + x
1 + x = x - 5 + x
1 + x = 2x - 5
Next, move terms:
1 + x = 2x - 5
(Move variable to the left side and change its sign)
1 + x -2x = -5
(move constant to the right side and change its sign)
x - 2x = -5 - 1
Next, collect like terms:
x - 2x = -5 - 1
-x = -5 - 1
(Calculate the difference_
-x = -6
Finally change the sign on both sides of the equation:
-x = -6
x = 6